Editorial: Changing livelihoods, vulnerability and COVID-19 pandemic - Upadhyaya, Rachana; Shrestha, Anushiya; Gupta, Divya (New Angle: Nepal Journal of Social Science and Public Policy, 2024)
No abstract available.